Comparative evaluation of pediatric rotary file system and a single file technique on the quality of root canal preparation on deciduous teeth: a combined in-vivo and in-vitro study - Bhanushali, Hemangi; Sodani, Vasudha; Shah, Anvi; Sarvaiya, Bhumi; Sharma, Devdatt; Chhabria, Parth (International Journal Of Community Medicine And Public Health, 2025)
Background: Pulpectomy is the conservative treatment that retains and preserves the primary tooth in the dental arch in its function and non-pathologic state until its exfoliation. Over recent years, pulpectomy has been performed using various instrumentation techniques. The aim of this study was to evaluate the instrumentation time, taper and quality of obturation using pediatric rotary file system and a single file technique. Methods: Pulpectomy was performed on 40 patients and 40 3D printed models of primary second molar for the study. Kedo-S rotary files, Pro AF Baby Gold rotary file system, Pro Taper Sx rotary file and Neo Endo Flex Orifice Opener rotary file were used for instrumentation. Immediate post-operative digital radiographs were taken to evaluate the quality of root filing, taper of canal and root canal instrumentation time was also recorded. Results: No significant difference was observed in taper and quality of obturation using pediatric rotary file system and a single file technique (p value > 0.05). On comparing mean instrumentation time Neo Endo Flex Orifice Opener rotary file took least time for instrumentation, the highest time taken for instrumentation was seen in Pro AF Baby Gold rotary file system, this was statistically significant (p value <0.001). Conclusions: With the use of modified rotary file system for pulpectomy in primary teeth, reduction in the instrumentation time has been appreciated.